Modified SEPIC DC-to-DC boost converter with high output-gain configuration for renewable applications - Muranda C.; Ozsoy E.; Padmanaban S.; Bhaskar M.S.; Fedk V.; Ramachandaramurthy V.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric inverters; Energy conversion; HVDC power transmission; Topology; BOOST converter; High gain; High-voltage converter; Photovoltaic; SEPIC converter; DC-DC converters